Persepsi Masyarakat terhadap Tingkat Keamanan Lingkungan dalam Menyikapi Maraknya Kasus Curanmor di Wilayah Hukum Polsek Biringkanaya Kota Makassar - Nasir, Nasir (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Motor vehicle theft is a form of crime that often occurs in urban areas and has a direct impact on people's sense of security. In the jurisdiction of the Biringkanaya Police Station of Makassar City, the rampant cases of motor vehicle theft have raised concerns and formed a negative public perception of the existing security system. This study aims to describe and analyze public perception of the level of environmental safety and the factors that affect it. The research method used is a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation of local residents who are directly or indirectly affected by the case of motor vehicle theft. The results of the study show that the majority of people feel worried and lack confidence in the effectiveness of environmental security, both from the police and citizens' initiatives. The lack of police patrols, the inactivity of patrol posts, and weak solidarity and social participation are the main factors that reinforce these negative perceptions. The novelty of this study lies in the emphasis on the subjective perception of the public as a key indicator in the evaluation of environmental security. The implications of this study emphasize the importance of a community policing approach as well as strengthening citizen involvement in community-based security systems to create a more sustainable sense of security.